Influence Work-life Balance and Person-organization Fit toward OCB: The Mediated Role Organizational Commitment - Kurniawan, Yudha Bagus; Rijanti, Tristiana (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The first aim of the paper was to investigate the impact work-life balance (WLF) toward organizational commitment, and the effect person-organization fit (POF) toward OCB. Second objective was to examine the mediation role of the organizational commitment in the relationship WLF and POF on OCB. The study design used the quantitative research with the survey method. The sample of this study was all 102 employees of the Transportation Agency in Pati Regency, Central Java, Indonesia. Data were analyzed using multiple linear regression and the Sobel test for mediation. The finding demostrated WLF had positive-significant effect toward the organizational commitment. Moreover, POF also had a positive-significant influence on the organizational commitment. Furthermore, WLB, POF, and the organizational commitment had a positive-significant influence toward OCB. Organizational commitment was proven to mediate role the effect the WLF on OCB, as well as the influence of POF on OCB.